The organizational commitment and its relation to certain demographic and psychological factors - Arias Galicia, Fernando (2003)
One looks for to know the relation that exists between the organizational commitment and some demographic variables (studied by Mathieu and Zajac) in a sample of 190 people with a high education, originating of diverse varied organizations and so large. Was high correlation between affective commitment and general satisfaction with the work, also between affective commitment and commitment with the work, just as affective commitment and clarity of the roll. However the relation with hierarchy of the position was not significant. On the other hand, the correlations between the convenience commitment and the other variables were inferior, being highest with clarity of the rol, followed by satisfaction with the work. However no of the demographic variables denoted important association with the convenience commitment. Neither sex nor the civil state denoted to exert influence some on the commitment.